2014
DOI: 10.1002/biot.201400306
|View full text |Cite
|
Sign up to set email alerts
|

A functional high‐content miRNA screen identifies miR‐30 family to boost recombinant protein production in CHO cells

Abstract: The steady improvement of mammalian cell factories for the production of biopharmaceuticals is a key challenge for the biotechnology community. Recently, small regulatory microRNAs (miRNAs) were identified as novel targets for optimizing Chinese hamster ovary (CHO) production cells as they do not add any translational burden to the cell while being capable of regulating entire physiological pathways. The aim of the present study was to elucidate miRNA function in a recombinant CHO-SEAP cell line by means of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 59 publications
2
90
0
Order By: Relevance
“…One plausible route might be post-transcriptional regulation by miRNAs, which is supported by the observation of numerous changes in miRNA expression in this study. Interestingly, miR-30 was found to be up-regulated in subclones characterized by high qP, which is in line with results from a recent high-throughput screen of miRNA overexpression in a CHO-SEAP cell line [65]. Therefore, a thorough integrative computational analysis of miRNA and mRNA expression data in the future could allow to identify miRNA~mRNA networks that support a high productivity state.…”
Section: Discussionsupporting
confidence: 82%
“…One plausible route might be post-transcriptional regulation by miRNAs, which is supported by the observation of numerous changes in miRNA expression in this study. Interestingly, miR-30 was found to be up-regulated in subclones characterized by high qP, which is in line with results from a recent high-throughput screen of miRNA overexpression in a CHO-SEAP cell line [65]. Therefore, a thorough integrative computational analysis of miRNA and mRNA expression data in the future could allow to identify miRNA~mRNA networks that support a high productivity state.…”
Section: Discussionsupporting
confidence: 82%
“…We recently conducted an unbiased functional miRNA screen in a recombinant CHO cell line assessing the impact of 1139 miRNAs on crucial cellular functions. 11 In this report, we demonstrate that each of these vital cellular pathways could be controlled by an unexpectedly large number of miRNAs, which may indicate a redundancy in pathway regulation guaranteeing survival of the cell. Since the pathways are to some degree interrelated, we found that subsets of miRNAs have both specific as well as overlapping functions.…”
Section: Introductionmentioning
confidence: 67%
“…Transfections of miRNA mimics and small interfering RNAs (siRNAs) were carried out essentially as described previously. 11 An entire murine miRNA mimics library (miRBase release 18) comprising 1139 different miRNAs was used for the transient miRNA screening (Qiagen, Hilden, Germany) (see also Supplementary Table S1). An Alexa Fluor Ò 647-labeled non-targeting siRNA, a non-labeled, scrambled siRNA (NT siRNA), an anti-SEAP siRNA (siSEAP) (all Qiagen) and a cell death control siRNA (siDeath) (kindly provided by Dr. Eric Lader, Qiagen) served as functional transfection controls.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify miRNAs able to increase recombinant protein production in Chinese hamster ovary (CHO) cells, the prototype mammalian cell line for production of biopharmaceuticals, Fischer and collaborators 43 performed a miRNA screening using a library of 1139 human miRNA mimics. In this study, the miR-30 family was recognized as a potent enhancer of protein production in CHO cells.…”
Section: V12mentioning
confidence: 99%